PENGARUH SUBSTITUSI TEPUNG BIT PADA PEMBUATAN BROWNIES KUKUS TERHADAP DAYA TERIMA KONSUMEN - Safira Salsabila; Nur Riska; Rusilanti Rusilanti (Syntax Idea)
Beet flour is used in the manufacture of steamed brownies to be an alternative as a natural dye, to increase the variety of beet flour products, to reduce the use of wheat flour, and to use beet flour as a functional local food. This study aims to study and analyze the effect of beet flour substitution in the manufacture of steamed brownies on the physical quality and consumer acceptance. This research was conducted at the Pastry and Bakery Processing Laboratory of the Culinary Education Study Program, State University of Jakarta. The time of the research starts from July 2021 to June 2022. The method used in this study is an experimental method. The research sample used was steamed brownies with beet flour substitution as much as 35%, 45% and 55%, then tested on 30 untrained panelists who assessed all aspects. Based on the results of statistical hypothesis testing using the Friedman test, it shows that in all aspects there is no effect of substitution of beet flour as much as 35%, 45% and 55% in steamed brownies on consumer acceptance in terms of color, aroma, sweet taste, beet taste, texture, moistness, and pores. The conclusion of this study is to recommend steamed brownies with 55% beet flour substitution to be developed because it is liked by consumers and optimizes the use of beet flour as a functional local food.